PERFORMANCE OF BROILER CHICKEN WITH ADDITION OF MAGGOT FLOUR IN FEED - Irindra Sekar Jalu; Hamong Suharsono; I Ketut Sumadi (Buletin Veteriner Udayana, 2025)
This study aimed to determine the effect of adding Black Soldier Fly (Hermetia illucens) maggot meal to commercial feed on the growth performance of broilers (Gallus domesticus), particularly body weight gain and feed conversion ratio (FCR). The research was conducted using a Completely Randomized Design (CRD) with four treatments: P0 (control), P1, P2, and P3, each with six replications. Broilers were raised from Day Old Chick (DOC) and fed BR I Crumbel feed from day 1 to 21 and BR II SP-Pellet from day 22 to 34. The maggot meal supplementation was given from day 14 to day 34. The results showed that the addition of Hermetia illucens maggot meal to commercial feed had no significant effect (P>0.05) on the broilers’ body weight gain or feed conversion ratio. Therefore, under the conditions of this study, the inclusion of maggot meal in the diet did not significantly improve the growth performance of broilers.